2014
DOI: 10.1021/la5012988
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrophobicity on Self-Assembly by Peptide Amphiphiles via Molecular Dynamics Simulations

Abstract: Using a novel coarse-grained model, large-scale molecular dynamics simulations were performed to examine self-assembly of 800 peptide amphiphiles (sequence palmitoyl-V3A3E3). Under suitable physiological conditions, these molecules readily assemble into nanofibers leading to hydrogel construction as observed in experiments. Our simulations capture this spontaneous self-assembly process, including formation of secondary structure, to identify morphological transitions of distinctive nanostructures. As the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 60 publications
4
48
0
Order By: Relevance
“…As the β-sheet forming peptide region become less hydrophobic as in the case of PA4, the ability to form stable one-dimensional nanofiborus structure with contiguous hydrophobic core is limited. This agrees with our previous studies that examine the effects of solventdependent hydrophobicity 44,45 and to some extent pHdependent electrostatics 10,42 on PA self-assembly.…”
Section: Discussionsupporting
confidence: 92%
“…As the β-sheet forming peptide region become less hydrophobic as in the case of PA4, the ability to form stable one-dimensional nanofiborus structure with contiguous hydrophobic core is limited. This agrees with our previous studies that examine the effects of solventdependent hydrophobicity 44,45 and to some extent pHdependent electrostatics 10,42 on PA self-assembly.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, in order for the formation of elongated cylindrical nanofibers, Velichko et al suggests that β-sheet formation acts as the nucleation step followed by the cooperative effect of hydrogen bonding between peptide segments and the hydrophobic collapse of alkyl tails. These results are also supported by recent CG simulation studies by Fu et al 82 as shown in Figure 3B that suggests with increasing hydrophobicity, PAs first aggregate into a network of β-sheets and then assemble into cylindrical nanofibers followed by cylindrical micelles. The necessity of β-sheets for cylindrical nanofiber assembly was further explored by a comparative study of two cylindrical nanofibers composed with two PA monomers (Alanine rich and Valine rich).…”
Section: Simulations Of Peptide-amphiphile Self-assembliessupporting
confidence: 87%
“…In the last decade, an increasing number of computational groups have provided major insights into the structure and self-assembly of PA nanofibers as shown in Table 1 and in discussed within the context of this review. 8,2033 …”
Section: Introductionmentioning
confidence: 99%
“…A phase diagram between electrostatics and temperature was constructed shown in Figure 13 for the delineating morphological regions in response to external stimuli (Fu et al, 2013). In terms of hydrophobicity, they observed the progressive transition from open network to closed cylindrical structure with increasing hydrophobicity (Fu et al, 2014). Furthermore, they examined solvent effects on peptide assembly.…”
Section: F4h5k15 F8h5k15 F12h5k15 F16h5k15mentioning
confidence: 99%